The Effectiveness of Green Roof Technology in Mosque Internal Space - Mohkatar, Muhd Hairee; Abdullah, Abdul Halid (Recent Trends in Civil Engineering and Built Environment, 2021)
The green roof is a system necessary to decrease thermal temperatures. This research aims to study the effectiveness of green roof technology on the thermal efficiency of the mosque’s interior space while evaluating the performance of green roof and conventional roof on the mosque’s external and internal surface.The research is conducted at the Masjid Kota Iskandar, Nusajaya, Johor which applied green roof technology. The aim of this research is to determine the effectiveness of the green roof to control the temperature of the exterior and interior of the building to reduce the air temperature of the room space that applies green roof technology. Infrared Thermometer and 4 In the 1 meter kit temperature readings are reported on the internal and external surfaces of the sun exposed roof. This tool reports readings on plots on green roofs and conventional roofs that have been identified. In the marked areas, a total of two readings were recorded. Based on the study that has been conducted, this study can be concluded that the green roof surface is able to reduce the average temperature on the room temperature 0.6 oC-1.3 oC compared to conventional roof surfacesThe results of this research shows that the temperature on the green roof is reduced compared to conventional roofs.. Therefore, this has achieved the main objective of the study which is to study the effectiveness of green roof technology on the thermal performance of mosque internal space.